Assessment of Load Manual Lifting among Shelf-Stoking Workers in Chain Stores: A Cross-Sectional Study - Choobineh, Alireza; Dortaj, Elahe; Razeghi, Mohsen; Ghaem, Haleh; Daneshmandi, Hadi (Applied Bionics and Biomechanics, 2024)
In Iranian stores, shelf workers, in addition to shelf-stocking, perform diverse tasks, such as working as a cashier, cleaning, barcode reading, labeling goods, and entering the price with the portable data terminal (PDT). Therefore, this study aimed to investigate the prevalence of work-related musculoskeletal symptoms (WMSs) and assess load manual lifting among shelf-stoking workers. This cross-sectional study was conducted among 101 shelf-stoking workers (60 males and 41 females) in chain stores at Shiraz city, Iran. The subjects were selected by cluster sampling from chain stores in Shiraz city, namely Refah, Canbo, Soroush, and Tirazis. Then, the required number of samples was selected and entered into the study from each cluster in proportion. The Persian version of the Nordic Musculoskeletal Questionnaire and the National Institute of Occupational Safety and Health–variable lifting index method were used to collect the required data. Data were analyzed by SPSS software version 22 using the Mann–Whitney U test, Spearman’s correlation coefficient, and linear regression. Ankles/feet, lower back, and knees had the highest prevalence of WMSs among the participants. About 70.3% of workers had a VLI higher than 1. There was an association between gender and VLI. The VLI was higher in males than females. The study’s findings revealed that the medians of the VLI were significantly different among participants with/without upper back symptoms during 12 months prior to the study and among participants with/without lower back symptoms during 7 days prior to the study. According to the linear regression analysis, gender and lower back symptoms during 7 days prior to the study remained in the model and were associated with the VLI. The findings revealed that the back region of the shelf-stoking workers is prone to work-related musculoskeletal disorders. In addition, based on the results, gender and lower back symptoms during the 7 days prior to the study were predicting variables for VLI. This study provides an overview of pain/discomfort and postural load in shelf-stoking workers. Since the principles of ergonomics for the placement and layout of shelves are the same in all stores, the findings of the present study can be used in other stores.